2020
DOI: 10.1038/s42003-020-0960-y
|View full text |Cite
|
Sign up to set email alerts
|

Timekeeping in the hindbrain: a multi-oscillatory circadian centre in the mouse dorsal vagal complex

Abstract: Metabolic and cardiovascular processes controlled by the hindbrain exhibit 24 h rhythms, but the extent to which the hindbrain possesses endogenous circadian timekeeping is unresolved. Here we provide compelling evidence that genetic, neuronal, and vascular activities of the brainstem's dorsal vagal complex are subject to intrinsic circadian control with a crucial role for the connection between its components in regulating their rhythmic properties. Robust 24 h variation in clock gene expression in vivo and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(119 citation statements)
references
References 64 publications
16
103
0
Order By: Relevance
“…Neuronal activity in the murine DVC exhibits daily and circadian changes, with higher levels at late day/early night ( Chrobok et al, 2020 ). Thus, here we assessed if phasic neurons in the NTS are amongst these potential timekeeping neurons.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Neuronal activity in the murine DVC exhibits daily and circadian changes, with higher levels at late day/early night ( Chrobok et al, 2020 ). Thus, here we assessed if phasic neurons in the NTS are amongst these potential timekeeping neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, we found that phasic activity pattern was not evenly distributed in the NTS – most of phasic neurons were localised in its dorsomedial part, in proximity to the AP. Our previous study found that in mice, this particular subdivision of the NTS has direct access to blood-borne information during the behaviourally active night, when the glial barrier between the AP and the NTS exhibits notable permeability ( Chrobok et al, 2020 ). Other studies localise aldosterone-sensing cells or neuropeptide Y-synthesising neurons in this NTS subdivision ( van den Pol et al, 2009 ; Resch et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations